Safe trabeculectomy technique: long term outcome. Issue 1 (16th December 2005) - Stalmans, I; Gillis, A; Lafaut, A-S; Zeyen, T
Abstract : Aim: To assess the long term outcome of a new trabeculectomy technique. Methods: Trabeculectomy was performed using a fornix based conjunctival flap, an anterior chamber maintainer, a standardised punch technique, and a combination of adjustable and releasable sutures in 56 eyes of 53 patients. The main outcome measures were the postoperative intraocular pressure (IOP) and the frequency of early postoperative complications. The mean follow up time was 15.7 (range 12–21) months. Results: The mean preoperative and postoperative IOP at 12 months were 21.2 (SD 6) and 12.8 (3.0) mm Hg, respectively. All patients had an IOP of <21 mm Hg, 90.9% had an IOP <18 mm Hg, and 61.4% had an IOP <14 mm Hg. Postoperative complications were infrequent: flat anterior chamber (1.8%), bleb leakage (0%), or hypotony (1.5%) beyond 3 weeks, or choroidal detachment at any time point (8.9%). Conclusions: This novel trabeculectomy method offers the possibility to tailor the IOP postoperatively with a minimum of postoperative complications and excellent IOP control at the long term follow up.